Avaliação dos aspectos das políticas públicas, socioeconômicos e hidrológicos-hidráulicos no uso de microrreservatórios - Pedro de Paula Drumond (2019)
In recent decades On-site Stormwater Detention (OSD) systems have been implemented in Brazilian cities and many other cities around the world. Despite the existence of public policies on the use of OSD, only a few studies have evaluated the technique in relation to the criteria used to design the structure, the citizens' mood to adopt OSD in their lots, the efficiency in the peak flow damping of the OSDs already built and the possibility of technique improvement. Thus, this study compared the public policies of Belo Horizonte and Porto Alegre with current policies in the Australian cities of Wollongong and Sydney, created in the 80’s. The results indicated that Australian municipalities require the peak flow damping for several rains (with different durations and return times), while the Brazilian cities request the design for only one event with a return time of 10 years. However, as the Brazilian cities, the Australian municipalities have problems in the system management, and do not have control of the quantity of OSDs already built in the cities and their conditions. To evaluate the population perception, it was decided to apply forms to the citizens of Belo Horizonte with questions about the drainage system operation and its problems, the urban drainage tax and the disposition to build the OSDs on lots. The results indicated that citizens did not know clearly that there is no exclusive tax for urban drainage service and the majority of answers (about 83%) are favorable to build OSDs on the lots, regardless of the financial incentives possibilities. As OSDs have been built in Belo Horizonte since the 90’s, it was decided to evaluate the performance of OSDs already built, comparing the maximum water levels monitored inside the structures with the results calculated using theoretical methods. It was verified that the values of theoretical simulations were lower than those monitored, and the results obtained with the Rational method were better than those calculated with UH-SCS method. Finally, two OSDs were built, one with impermeable bottom and other with permeable bottom. The OSDs monitoring indicated that the technique could have good efficiency in the peak flow damping. The average efficiency in the peak flow damping obtained in the OSD with permeable bottom was approximately 87%. After the all analyzes with the data of the experiments, a new proposal was presented for the OSD design.